Beta cell regeneration upon magainin and growth hormone treatment as a possible alternative to insulin therapy - Azam Moosavi; Razieh Yazdanparast (FEBS Open Bio, 2023)
Insulin therapy, pancreas transplantation and β cell regeneration are among the suggested treatment strategies for type 1 diabetes. It has been shown that some antimicrobial peptides have the potential to increase insulin release and to improve glucose tolerance, although the mechanism by which they promote the regeneration of damaged pancreatic cells to functional β‐like cells remains unknown. To answer this question, we evaluated the in vivo effects of magainin‐AM2 and growth hormone (GH) on the regeneration of streptozotocin (STZ)‐damaged mouse pancreas. Treatment with magainin‐AM2 and GH ameliorated the effects of STZ on fasting blood glucose and glucose tolerance test values, and also resulted in a significant increase in total cell counts (α and β) and the number of insulin+ and glucagon+ cells per islet and a decrease in the number of T and B cells. In addition, we observed a 1.43‐ and 2.21‐fold increase in expression of paired box 4, one of the main factors for α to β‐like cell conversion, in normal‐ and diabetes‐treated mice, respectively. Similarly, expression of P‐S6 and extracellular signal‐regulated kinases 1 and 2, required for cell proliferation/differentiation, increased by 3.27‐ and 2.19‐fold among the diabetes‐treated and control diabetic mice, respectively. Furthermore, in all experiments, amelioration of the effects of STZ were greatest upon Mag treatment followed by GH administration. The present in vivo data provide evidence in support of the possibility of pharmaceutical induction of α cell production and their trans‐differentiation to functional β‐like cells.